2017
DOI: 10.1002/clen.201700238
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fungi Against Aquaculture Pathogens and Induction of the Activity via Co‐Culture

Abstract: Ethyl acetate extracts from 70 strains of marine-derived fungi, isolated from sponges, were screened against four fish pathogenic bacteria. Sixteen of the fungal isolates exhibited antibacterial activity against at least one pathogen. All the strains showed antibacterial activity against Vagococcus salmoninarum. Three isolates showed strong inhibition against all test pathogens and they may therefore be remarkable as a broadspectrum antimicrobial. Nine isolates showed antibacterial activity against Lactococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The natural product ergosta‐4,6,8(14),22‐tetraene‐3‐one obtained from deep sea‐derived fungi Aspergillus penicillioides showed strong inhibitory activity against the pathogenic bacteria Edwardsiella tarda 286 . The fungus Penicillium canescens , isolated from the marine sponge Cacospongia sp., collected from the Aegean Sea Coast of Turkey, revealed activity against Yersinia ruckeri , however, the bioactive compounds were not isolated nor identified 69 . Two chamigrene derived sesquiterpenoids isolated from the red seaweed Laurencia chondrioides , demonstrated antimicrobial bioactivity against Pseudomonas anguilliseptica 298 .…”
Section: Added Value Activities For Novel Aquafeedmentioning
confidence: 96%
See 3 more Smart Citations
“…The natural product ergosta‐4,6,8(14),22‐tetraene‐3‐one obtained from deep sea‐derived fungi Aspergillus penicillioides showed strong inhibitory activity against the pathogenic bacteria Edwardsiella tarda 286 . The fungus Penicillium canescens , isolated from the marine sponge Cacospongia sp., collected from the Aegean Sea Coast of Turkey, revealed activity against Yersinia ruckeri , however, the bioactive compounds were not isolated nor identified 69 . Two chamigrene derived sesquiterpenoids isolated from the red seaweed Laurencia chondrioides , demonstrated antimicrobial bioactivity against Pseudomonas anguilliseptica 298 .…”
Section: Added Value Activities For Novel Aquafeedmentioning
confidence: 96%
“…Moreover, several publications recently demonstrated that marine fungi are a source of antimicrobial compounds for use in aquaculture against fish pathogens. Fungi from sponges have been screened for the production of antimicrobial compounds active against different fish pathogens, that is, Lactococcus garvieae , Vibrio anguillarum , Vibrio harveyi , Yersinia ruckeri and Vagococcus salmoninarum 68–71 . Since bacterial pathogens are a serious threat in aquaculture and the antimicrobial resistance in cultured aquatic animals is at concerning levels, 72 there is an increasing need for new tools and approaches to manage aquaculture sustainably.…”
Section: Microorganisms As Single‐cell Ingredientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspergillus iizukae is present in various environments, such as leaves of Silybum marianum [ 1 ], sponges [ 2 ], guts of a cricket species Gryllus testaceus [ 3 ], earthworm casts and different kinds of soil [ 4 ]. Recently, Özkaya et al found that the ethyl acetate extract of a sponge-associated A. iizukae showed inhibitory effects against the aquaculture pathogens Lactococcus garvieae and Vagococcus salmoninarum [ 2 ]. Additionally, a novel flavin adenine dinucleotide-dependent glucose dehydrogenase was separated from the culture of A. iizukae , which was capable of catalyzing the oxidation of glucose to glucono-δ-lactone [ 5 ].…”
Section: Introductionmentioning
confidence: 99%